STRATEGI PUBLIC RELATION DALAM MENGATASI PERMASALAHAN DISTRIBUSI DAN PENURUNAN TARGET PENJUALAN PADA USAHA TANDON AIR PT SINAR PUTRA MEGAH - Putri Elen Aulia Rahmadani; Ariyan Alfraita (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze public relations strategies for addressing distribution issues and declining sales targets at PT Sinar Putra Megah, a water tank business. The company's challenges include disrupted product distribution and failure to achieve established sales targets, which are suspected to be influenced by weak communication with distribution partners and consumers. This study employed a qualitative method with a descriptive case study approach. Data collection techniques included in-depth interviews, direct observation, and a review of company documents. Data analysis employed the Miles and Huberman model of data reduction, data presentation, and conclusion drawing. The results indicate that distribution issues are not merely technical in nature but also lead to misunderstandings and a decline in trust among partners and consumers. The implemented public relations strategy plays a crucial role as a communication bridge to convey information transparently, explain challenges, and rebuild trust. This study concludes that a structured and integrated public relations strategy with technical improvements to the distribution system can be an effective solution for restoring smooth distribution and gradually increasing the company's sales target achievement. Keywords: Public Relations Strategy, Distribution, Sales Decline, Water Tanks, Qualitative Method